Amnestus mendeli sp. n., the first burrower bug species (Hemiptera: Heteroptera: Cydnidae) recorded on Ascension Island, central Atlantic Ocean - Lis, Jerzy A.; Lis, Barbara (Zootaxa, 2016)
A new species of the genus Amnestus Dallas, 1851, Amnestus mendeli, is described from the cloud zone of Green Mountain, Ascension Island, and compared with its closest relatives, the Brazilian Amnestus lenkoi Froeschner, 1975 and Amnestus pequinus Froeschner, 1975. It is the first representative of the family Cydnidae recorded on the island thus far. The species is presumed to be an introduction from the Americas, but the hypothesis that it might be endemic to Ascension Island is also not excluded.